Levantado do chão de José Saramago e Nenhum olhar de José Luís Peixoto: uma leitura do espaço narrativo - Campos, Juliana Sant'Ana (2009)
The main objective of this study is to present a reading of the narrative space in two contemporary Portuguese novels, one of them is Levantado do Chão by José Saramago (2005) and the other, Nenhum Olhar by José Luís Peixoto (2005). In both novels, the analyzed space is Alentejo, presented as a place that the limit between life and death is faint. The writers also use such space to reflect about specific questions of this area. In both plots, the store of the characters is develop by generations in which the pain cycle of pain and/or work need to be broken. Each action unleashed by a character, in a specific place, bringing on significant changes for the space of the plot as a whole. To develop the analyze of the space the theoretical criticism proposals belonging to Gaston Bachelard and Antonio Dimas were used, as well as those related to utopia and dystopia from Carlos Eduardo Ornelas Berriel, Lyman Tower Sargent, Tomas More, Ildney Cavalcanti, J. M. Sousa Nunes, and nihilism from Rossano Pecoraro. The conceptions related to utopia and dystopia, however, were used basically to analyze Levantado do Chão and reveled that the novel varies between the two genders. At the beginning, Saramago s book was based on the dystopic gender for, latter, change to utopic. The nihilism conception, in turn, was used to study the novel Nenhum Olhar, because this is based in the absolutely nothing, not presenting any possibility of future for the characters. Finally, both were compared and common points were reveled, such as the absence of God, the change of nature that follows the change of the plot and the constructions of a space named Alentejo made as criticism and imagination